Quantification of Glycosaminoglycans in Urine by Isotope‐Dilution Liquid Chromatography‐Electrospray Ionization Tandem Mass Spectrometry. Issue 3 (16th March 2023) - Zhang, Haoyue; Young, Sarah P.; Millington, David S.
Abstract: Mucopolysaccharidoses (MPSs) are complex lysosomal storage disorders that result in the accumulation of glycosaminoglycans (GAGs) in urine, blood, and tissues. Lysosomal enzymes responsible for GAG degradation are defective in MPSs. GAGs including chondroitin sulfate (CS), dermatan sulfate (DS), heparan sulfate (HS), and keratan sulfate (KS) are disease‐specific biomarkers for MPSs. This article describes a stable isotope dilution‐tandem mass spectrometric method for quantifying CS, DS, and HS in urine samples. The GAGs are methanolyzed to uronic or iduronic acid‐N‐acetylhexosamine or iduronic acid‐N‐sulfo‐glucosamine dimers and mixed with internal standards derived from deuteriomethanolysis of GAG standards. Specific dimers derived from HS, DS, and CS are separated by ultra‐performance liquid chromatography (UPLC) and analyzed by electrospray ionization tandem mass spectrometry (MS/MS) using selected reaction monitoring for each targeted GAG product and its corresponding internal standard. This UPLC‐MS/MS GAG assay is useful for identifying patients with MPS types I, II, III, VI, and VII. © 2023 Wiley Periodicals LLC. Basic Protocol : Urinary GAG analysis by ESI‐MS/MS Support Protocol 1 : Prepare calibration samples Support Protocol 2 : Preparation of stable isotope‐labeled internal standards Support Protocol 3 : Preparation of quality controls for GAG analysis in urine Support Protocol 4 : Optimization of the methanolysis time Support Protocol 5 : Measurement of the concentration of methanolic HCl